Tbet Expression in Regulatory T Cells Is Required to Initiate Th1-Mediated Colitis - Di Giovangiulio, Martina; Rizzo, Angelamaria; Franzè, Eleonora; Caprioli, Flavio; Facciotti, Federica; Onali, Sara; Favale, Agnese; Stolfi, Carmine; Fehling, Hans-Joerg; Monteleone, Giovanni; Fantini, Massimo C. (Frontiers in Immunology, 2019)
In normal conditions gut homeostasis is maintained by the suppressive activity of regulatory T cells (Tregs), characterized by the expression of the transcription factor FoxP3. In human inflammatory bowel disease, which is believed to be the consequence of the loss of tolerance toward antigens normally contained in the gut lumen, Tregs have been found to be increased and functionally active, thus pointing against their possible role in the pathogenesis of this immune-mediated disease. Though, in inflammatory conditions, Tregs have been shown to upregulate the T helper (Th) type 1-related transcription factor Tbet and to express the proinflammatory cytokine IFN-gamma, thus suggesting that at a certain point of the inflammatory process, Tregs might contribute to inflammation rather than suppress it. Starting from the observation that Tregs isolated from the lamina propria of active but not inactive IBD patients or uninflamed controls express Tbet and IFN-gamma, we investigated the functional role of Th1-like Tregs in the dextran sulphate model of colitis. As observed in human IBD, Th1-like Tregs were upregulated in the inflamed lamina propria of treated mice and the expression of Tbet and IFN-gamma in Tregs preceded the accumulation of conventional Th1 cells in the lamina propria. By using a Treg-specific Tbet conditional knockout, we demonstrated that Tbet expression in Tregs is required for the development of colitis. Indeed, Tbet knockout mice developed milder colitis and showed an impaired Th1 immune response. In these mice not only the Tbet deficient Tregs but also the Tbet proficient conventional T cells showed reduced IFN-gamma expression. However, Tbet deficiency did not affect the Tregs suppressive capacity in vitro and in vivo in the adoptive transfer model of colitis. In conclusion here we show that Tbet expression by Tregs sustains the early phase of the Th1-mediated inflammatory response in the gut.